Development of a core outcome set for congenital pulmonary airway malformations: study protocol of an international Delphi survey. Issue 4 (12th April 2021) - Hermelijn, Sergei; Kersten, Casper; Mullassery, Dhanya; Muthialu, Nagarajan; Cobanoglu, Nazan; Gartner, Silvia; Bagolan, Pietro; Mesas Burgos, Carmen; Sgro, Alberto; Heyman, Stijn; Till, Holger; Suominen, Janne; et al.
Abstract : Introduction: A worldwide lack of consensus exists on the optimal management of asymptomatic congenital pulmonary airway malformation (CPAM) even though the incidence is increasing. Either a surgical resection is performed or a wait-and-see policy is employed, depending on the treating physician. Management is largely based on expert opinion and scientific evidence is scarce. Wide variations in outcome measures are seen between studies making comparison difficult thus highlighting the lack of universal consensus in outcome measures as well. We aim to define a core outcome set which will include the most important core outcome parameters for paediatric patients with an asymptomatic CPAM. Methods and analysis: This study will include a critical appraisal of the current literature followed by a three-stage Delphi process with two stakeholder groups. One surgical group including paediatric as well as thoracic surgeons, and a non-surgeon group including paediatric pulmonologists, intensive care and neonatal specialists. All participants will score outcome parameters according to their level of importance and the most important parameters will be determined by consensus. Ethics and dissemination: Electronic informed consent will be obtained from all participants. Ethical approval is not required. After the core outcome set has been defined, we intend to design an international randomised controlled trial: the COllaborative Neonatal NEtwork for the first CPAM Trial, which will be aimed at determining the optimal management of patients with asymptomatic CPAM.